Heavy λ semileptonic decay: A QCD sum rule approach - Dosch, H. G.; Ferreira, E.; Nielsen, M.; Rosenfeld, Rogério [UNESP] (Elsevier B.V., 1999)
In this work we calculate the form factors of the Lambda(c) and Lambda(b) semileptonic decay using the QCD sum rules approach. We found that the form factors sum rules are more stable than the respective mass sum rules, and we get a decay rate for Lambda(c) compatible with experiment.